Sheer Presence : The Veil in Manet's Paris - Kessler, Marni Reva (Book collections on Project MUSE., 2006)
In Sheer Presence, Marni Reva Kessler demonstrates how the ubiquitous veil and its visual representations knot together many of the precepts of Parisian life. Positioning the veil directly at the intersection of feminist, formalist, and social art history, Kessler offers a fresh perspective on period discourses of public health, seduction and sexuality, colonial stereotypes, and, ultimately, an emerging modernity.